Old Leather: An Oral History of Early Pro Football in Ohio, 1920-1935 - Willis, Chris (Rowman & Littlefield Publishers, 2005)
Very little has been documented about the early days of pro football and the pioneers who had a major influence in the history of the NFL. Chris Willis, head of the Research Library at NFL Films, seeks to address this neglect. In this collection of original and archival interviews, former players, owners, fans, family members and league officials provide a rare glimpse into the origins of professional football. Full of rich anecdotes, early stars such as Red Grange, Jim Thorpe, Dutch Clark, Glenn Presnell, and Pete Henry are brought back to the playing field. The interviews also reveal how small towns in Ohio such as Canton, Akron, Columbus, and Dayton came to host franchises, as the state became a major force in the founding and growth of the NFL. Old Leather provides the reader with a firsthand look at a period that has largely been ignored. It recalls what the era of professional football was like in the age of leather helmets, no television, dirt fields, small salaries and when playing for the love of the game was its own reward. This book will appeal not only to historians, sportswriters, and scholars, but also to die-hard fans and general history buffs who can never get enough of America's favorite sport. Contains 17 photographs of players, owners, and teams.